(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. L’epidemia nel Codice civile italiano - 2. “Una brutta notizia, avvolta in una proteina” - 3. Le misure di contenimento dell’epidemia da Covid-19 adottate e l’esordio di vaccini anti-Covid-19 - 4. La vaccinazione obbligatoria: precedenti storici italiani - 5. La vaccinazione obbligatoria contro il Covid-19, oggi: una mappa mondiale - 6. La vaccinazione contro il Covid-19 in Italia: obbligo, diritto od onere? 7. Il problema della compatibilità dell’obbligo vaccinale con il quadro normativo costituzionale ed europeo - 8. Conclusioni. The introduction of a compulsory vaccination in Italy: critical profiles ABSTRACT: The multiple Covid-19 vaccines developed until now are typically thought of as the only means to meet the challenges posed by the current pandemic. The Italian legal system offers a composite framework for the regulation of vaccinations against Covid-19 and more precisely provides for the burden of vaccination for many categories of people (including healthcare workers). The purpose of this paper is to verify the legitimacy of a compulsory vaccination in the light of Italian and European sources of law. In this perspective, the Author argues that a compulsory vaccination against Covid-19 could be considered not consistent with both the Italian Constitution and the European legislation. Furthermore, the Author focuses on the phenomenon of vaccine esitancy, questioning whether a policy of mandatory vaccination is the proper tool for supporting the effective implementation of vaccination strategies.